Selection of The Regulatory Seaport Cybersecurity Based on Integrated AHP and Topsis - Rudiah Md Hanafiah; Mohd Azhafiz Abdullah; Izyan Munirah Mohd Zaideen; Ahmad Fayas Ahmad Najib; Noorul Shaiful Fitri Abdul Rahman; Nur Hazwani Karim (Asian Academy of Management Journal, 2025)
The digitisation of seaports has brought about a significant improvement in efficiency, productivity, and communication within the maritime industry. However, the increasing reliance on technology exposes seaports to cyber threats, constituting significant risk to the economy and national security. This paper addresses the critical need for seaports to implement robust cybersecurity measures. While digital advancements offer numerous advantages, the potential vulnerability to cyberattacks demands a strategic decision-making model for selecting effective seaport cybersecurity strategies. The proposed decision support model integrates the Analytical Hierarchy Process-Technique for Order Preference by Similarity to Ideal Solution (AHP-TOPSIS). AHP is employed to measure the relative importance of evaluation criteria of seaport cyber threat factors in this decision hierarchy. Subsequently, TOPSIS is applied to rank the cyber threat strategy alternatives. The novelty lies in providing decision-makers with a comprehensive approach that extends beyond technical solution. The results present decision-makers with non-technical strategies, including employee training, awareness program, and educational level, which have the potential to mitigate the technology-related cybersecurity risks more effectively in seaports. This research provides vital insights essential for developing efficient cybersecurity regulations for seaports, thereby strengthening national security and economic stability. By integrating the significance of non-technical measures with conventional technical methodologies, decision-makers can establish a more robust cybersecurity framework. The paper introduces a holistic approach that establishes a fundamental basis for developing comprehensive and adaptable cybersecurity strategies within the maritime industry.